2012
DOI: 10.1111/j.1467-6419.2011.00719.x
|View full text |Cite
|
Sign up to set email alerts
|

Trade Diversification, Income, and Growth: What Do We Know?

Abstract: This paper surveys the empirical literature on export and import diversification and its linkages with growth. We review widely used measures of diversification and the evidence about their evolution focusing on how export diversification relates to trade liberalization and economic development. We also discuss the linkages between trade diversification and productivity at the firm and industry level, highlighting new advances on the linkages between import diversification and productivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(131 citation statements)
references
References 160 publications
(235 reference statements)
4
122
1
4
Order By: Relevance
“…Examples include Amurgo Pacheco (2006), Kohler (2006, 2010), Feenstra and Kee (2007), Dutt et al (2011) and Dennis and Shepherd (2011). Cadot et al (2012) offer an excellent overview of the literature.…”
Section: Generalized System Of Preferencesmentioning
confidence: 99%
“…Examples include Amurgo Pacheco (2006), Kohler (2006, 2010), Feenstra and Kee (2007), Dutt et al (2011) and Dennis and Shepherd (2011). Cadot et al (2012) offer an excellent overview of the literature.…”
Section: Generalized System Of Preferencesmentioning
confidence: 99%
“…We try to find support for this conjecture by interacting the network effect with Rajan and Zingales' measure of financial dependence at the product level (Rajan and Zingales 1998). 12 We construct our r p variable at the product level by assigning to each product the Rajan-Zingales index of the ISIC code to which that product belong, using concordance tables between HS6 and ISIC3. We indeed find that the interaction term r p × ln n pdt has a positive and significant coefficient.…”
Section: Extensionsmentioning
confidence: 99%
“…The impact of trade liberalization on export diversification in the previous studies have not been conclusive (Cadot et al 2013). Some studies have found that trade openness leads to specialization instead of diversification as countries trade in the products in which they have comparative advantage (Ferdous 2011) while other studies have shown that trade liberalization increases export opportunities by increasing the number of trade partners, therefore increasing volume and diversity of demand for its products, resulting in increased export diversification (Agosin et al 2012).…”
Section: Foreign Direct Investment and Trade Opennessmentioning
confidence: 96%